PENGARUH PELATIHAN BENCANA DAN KESELAMATAN KERJA TERHADAP RESPONS PERSEPSI MAHASISWA PRODI ILMU KESEHATAN MASYARAKAT - Tri Niswati Utami; Meutia Nanda (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2019)
ABSTRACT Disasters are categorized as 2, namely natural disasters and non-natural disasters. Natural disasters such as earthquakes, tsunamis, floods, landslides, fires. Non-natural disasters such as accidents at work, accidents at home, schools, boarding schools, campuses, shopping, roads and so forth. The aim of the study: to analyze the effect of disaster and work safety training on students' perceptions of knowledge and attitudes toward disaster risk The sample is a student of the public health study program at the State Islamic University of North Sumatra Medan. Data analysis with t-test. The results of the study: there was a significant effect of disaster and safety training on perceptual responses of student knowledge p-value of 0.0001 <0.05. There is a significant effect of disaster and occupational safety training on the perceptual responses of students' attitudes of p-value of 0.0001 <0.05. Knowledge and attitude cannot be separated. These two things are interconnected, with the knowledge of earthquake disaster preparedness it will affect one's attitude when a disaster occurs. The training stimulus builds a positive perception response. Disaster training is more effective and acceptable when combined with work safety and health material in the campus environment so that respondents are more easily accepted. Conclusion: modification of disaster management and occupational health safety training is more easily understood by respondents. So that it effectively changes the respondents' knowledge and attitudes. The success of training as a means of changing knowledge and attitudes is determined by internal and external factors. Suggestion: implementation of safety and health at the university level needs to be done, to minimize the risk of accidents. Keywords: disaster training, occupational safety and health, perceptual responses, knowledge, attitudes.